2017
DOI: 10.1002/adma.201605290
|View full text |Cite
|
Sign up to set email alerts
|

All‐Vacuum‐Deposited Stoichiometrically Balanced Inorganic Cesium Lead Halide Perovskite Solar Cells with Stabilized Efficiency Exceeding 11%

Abstract: Vacuum-sublimed inorganic cesium lead halide perovskite thin films are prepared and integrated in all-vacuum-deposited solar cells. Special care is taken to determine the stoichiometric balance of the sublimation precursors, which has great influence on the device performance. The mixed halide devices exhibit exceptional stabilized power conversion efficiency (11.8%) and promising thermal and long-term stabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
221
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(233 citation statements)
references
References 43 publications
(60 reference statements)
9
221
0
3
Order By: Relevance
“…This indicates that the photons excite electrons and holes out of the inorganic metal halide atoms, which is consistent with the density functional theory (DFT) calculations that the corner interstitial cations, whether organic or inorganic, do not directly contribute to the band-edge states (17). However, the efficiency of the purely inorganic perovskites is currently at ∼11% (18)(19)(20), which is far below 22% of HOIP-based solar cells. This suggests that the presence of organic cation may be the key for achieving high solar cell efficiency.…”
supporting
confidence: 77%
“…This indicates that the photons excite electrons and holes out of the inorganic metal halide atoms, which is consistent with the density functional theory (DFT) calculations that the corner interstitial cations, whether organic or inorganic, do not directly contribute to the band-edge states (17). However, the efficiency of the purely inorganic perovskites is currently at ∼11% (18)(19)(20), which is far below 22% of HOIP-based solar cells. This suggests that the presence of organic cation may be the key for achieving high solar cell efficiency.…”
supporting
confidence: 77%
“…[24,29] All these reports suggested that the up to 260 C or even higher temperature was almost necessary for fabricated high performance allinorganic CsPbX 3 perovskite. However, such high annealing temperature would affect the fabrication of all-inorganic perovskite and limit their application, rendering the conversion impractical for many device architectures and substrates, such as temperature sensitive polymer substrate and c-Si solar cells relevant for tandem cell applications.…”
mentioning
confidence: 99%
“…Generally, the yellow-to-black phase transformation occurs at temperatures of above 300 C. [23][24][25][26] A recent investigation on the crystal behavior of CsPbI 3Àx Br x prepared by one step method indicated that the phase-pure CsPbI 2 Br can be obtained only the annealing temperature exceeds %260 C. [27] Similarly, in 2-step method to fabricate all-inorganic perovskite, the phase-pure all-organic perovskite can be acquired when the film annealed at 250 C for 10 min and then an additional 3 min at 350 C. [28] Besides, the gas-assisted and allvacuum-deposited all-inorganic CsPbI 2 Br also need the subsequent >320 C annealing process. [24,29] All these reports suggested that the up to 260 C or even higher temperature was almost necessary for fabricated high performance allinorganic CsPbX 3 perovskite. However, such high annealing temperature would affect the fabrication of all-inorganic perovskite and limit their application, rendering the conversion impractical for many device architectures and substrates, such as temperature sensitive polymer substrate and c-Si solar cells relevant for tandem cell applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a Pb-free solution with the high PCE has not been obtained to date. To improve short-term and long-term stabilities, several modifications were made to the device structure and processing methods [23,24]. As of November 2017, researchers from Korea Research Institute of Chemical Technology hold the record PCE for a single-junction PSC with 22.7% [25].…”
Section: Introductionmentioning
confidence: 99%